2018
DOI: 10.1111/odi.12702
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastoma—Clinical, radiological, and therapeutic findings

Abstract: Ameloblastoma are the most common odontogenic tumor. As they usually do not form metastasis, they are considered as benign tumors with a locally invasive growth pattern and destruction of the jaws and the surrounding tissue (Oral Diseases, 23, 2017, 199). This article focuses on clinical, radiological, and therapeutic findings, which may influence diagnosis and treatment of ameloblastoma in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
77
0
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 26 publications
0
77
0
20
Order By: Relevance
“…Recurrence rates range from 0% to 15%. A survey of the literature indicates that radical resection is the best treatment approach (Kreppel & Zoller, ). The most appropriate treatment for AM‐BC, based on all available treatments, has not been definitively established, because very few cases of AM‐BC have been reported; moreover, a valid statistical analysis to predict the prognosis or success of different treatment modalities has not been performed (Reichart, Philipsen, & Sonner, ; Ueda & Kaneda, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence rates range from 0% to 15%. A survey of the literature indicates that radical resection is the best treatment approach (Kreppel & Zoller, ). The most appropriate treatment for AM‐BC, based on all available treatments, has not been definitively established, because very few cases of AM‐BC have been reported; moreover, a valid statistical analysis to predict the prognosis or success of different treatment modalities has not been performed (Reichart, Philipsen, & Sonner, ; Ueda & Kaneda, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to ameloblastoma (Effiom, Ogundana, Akinshipo, & Akintoye, ; Kreppel & Zöller, ), CEOT has a predilection for the mandible, with a proportion of at least 1.4:1, and most lesions develop in the posterior region, with tooth association in almost 50% of cases (Chrcanovic & Gomez, ). Our data concur with findings of previous case series of CEOT, which have demonstrated that more than 65% of cases occur in the mandible (Abrams & Howell, ; Ai‐Ru, Zhen, & Jian, ; Azevedo et al., ; Chen et al., ; Franklin & Hindle, ; Krolls & Pindborg, ; Vap, Dahlin, & Turlington, ).…”
Section: Discussionmentioning
confidence: 99%
“…O ameloblastoma é um tumor benigno, localmente invasivo, originário do epitélio odontogênico [1][2][3] . É a neoplasia odontogênica mais comum.…”
unclassified
“…É a neoplasia odontogênica mais comum. Podem surgir dos restos da lâmina dentária, de um órgão do esmalte, do epitélio de cistos odontogênicos ou das células basais da mucosa oral [1][2][3] . Esta patologia não possui marcada predileção por raça ou gênero, e costuma acometer mais adultos jovens, entre a segunda e quarta décadas de vida [1][2][3][4] .…”
unclassified
See 1 more Smart Citation